Apakah Kepuasan Kerja Yang Dirasakan Dapat Memediasi Efek Kecerdasan Emosional Dan Mutasi Pekerjaan Terhadap Performa Karyawan? - Afiuddin, Muhammad Rifaldy; Kadir, Muh. Akob; Sohilauw, Muhammad Irfai (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
The study aims to test and analyze the relationship between the effect of emotional intelligence and work mutations on employee performance mediated by perceived job satisfaction. The type of research used is the quantitative approach, the population in this study is the entire employee who works at Astra Daihatsu Makassar Urip Sumoharjo which amounts to 52 employees, the sampling technique used in this research is using the total sample, where the entire number of population in the study is used as. The analysis used in hypothesis testing is path analysis with the help of Smart PLS 3 software. The results of the analysis provide evidence that the emotional intelligence that an employee possesses cannot support the creation of employee performance, but in other parts it has been shown to increase employee job satisfaction. Implementation of mutations has been proven to improve employee job satisfaction and work performance. Creation of high performance can be done by increasing employee satisfaction in work. The role of job satisfaction as a mediator in explaining the effects of emotional intelligence and the implementation of mutations has proven to have a meaningful impact in the creation of higher-directional employee performance